Common microbial aetiology of abnormal vaginal discharge among sexually active women in Dhaka, Bangladesh - Yusuf, Md Abdullah; Chowdhury, Mahmuda; Islam, KM Shahidul; Eva, Eliza Omar; Sharif, Ahmad Raihan; Rahman, Md Khalilur; Talukder, Abdur Rabban; Begum, Sahin Ara (South East Asia Journal of Public Health, 2013)
Abnormal vaginal discharge is a common symptom of genital infection in women. The aim of the present study was to evaluate the various causes of vaginal discharge in sexually active females. A cross-sectional study was undertaken among women aged 15 to 45 years with abnormal vaginal discharge, with or without itching attended at Sir Salimullah Medical College, Dhaka for a period of 6 months. After making the clinical diagnosis, appropriate tests for diagnosing candidiasis, trichomoniasis, gonorrhea and bacterial vaginosis were done. Among all patients, organisms responsible for abnormal vaginal discharges were found in 94.8% of the cases, of which vaginal candidiasis (53.6%) was the most common, followed by bacterial vaginosis (29.2%), trichomoniasis (10.8%), gonorrhea (1.2%) and non-specific other urogenital causes (5.2%). The most common age groups affected by vaginal candidiasis, bacterial vaginosis and trichomoniasis were 26-35 years (64.9%), 26-35 years (27.6%) and 15-25 years (52%) respectively. Gonorrhea was recorded in the age group of 15-25 years (66.7%). Most of the organisms were isolated in the age group of 30-40 years. The causative agent of vaginal candidiasis was the leading cause of vaginal discharge in the age group of sexually active women and next to it was the bacterial vaginosis. A lower rate of Trichomonas vaginalis was found in our study in comparison to other studies. DOI: http://dx.doi.org/10.3329/seajph.v1i1.13211 South East Asia Journal of Public Health 2011:1:35-39